2017
DOI: 10.15406/jccr.2017.09.00316
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine Supplementation in Patients with Chronic Heart Failure Receiving Optimum Medical Treatment

Abstract: Background: Thiamine deficiency may cause heart failure and symptoms including edema, palpitation, tachycardia, weakness, malaise, and dyspnea due to water and salt retention and peripheral vasodilation. Patients with heart failure might be thiamine deficient and benefit thiamine supplementation. This study was designed to evaluate the effect of thiamin supplementation on some systolic and diastolic echocardiographic parameters and signs and symptoms of heart failure.Methods: Fifty two patients with systolic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
(26 reference statements)
1
9
1
Order By: Relevance
“…In this pilot trial of thiamine supplementation in older adults with HFrEF, we were unable to recruit the target number of patients within 11 months, but our other feasibility targets were reached, including retention, refusal, and adherence rates. Similar to a recent parallel group thiamine trial [8], our study did not identify statistically significant benefits of thiamine supplementation, despite using a higher daily dose (500mg) than previous trials (100-300mg) [7,8,[19][20][21]. The use of sensitive markers such as peak GLS on echocardiography and NT-proBNP reveal non-significant improvement with supplementation over 3 months.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In this pilot trial of thiamine supplementation in older adults with HFrEF, we were unable to recruit the target number of patients within 11 months, but our other feasibility targets were reached, including retention, refusal, and adherence rates. Similar to a recent parallel group thiamine trial [8], our study did not identify statistically significant benefits of thiamine supplementation, despite using a higher daily dose (500mg) than previous trials (100-300mg) [7,8,[19][20][21]. The use of sensitive markers such as peak GLS on echocardiography and NT-proBNP reveal non-significant improvement with supplementation over 3 months.…”
Section: Discussionsupporting
confidence: 66%
“…A meta-analysis of two small placebo-controlled trials (pooled n=38) showed a small improvement (absolute increase of 3.28%, 95% confidence interval [CI] 0.64-5.93) in left ventricular ejection fraction (LVEF) with thiamine doses of 200-300mg/day [6]. Another trial of 50 stable HFrEF patients (mean age 61.4 years) showed no change to LVEF after 1 month of thiamine supplementation (300mg/day), but there was an improvement in patient-reported peripheral edema [7]. A recent trial of 69 stable HFrEF patients (mean age 56.7 years) found no changes in LVEF and NT-proBNP after 6 months of thiamine supplementation (200mg/day) [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the trial led by Seligmann et al in the nineties showed that the beneficial effect of thiamine on left ventricular ejection fraction was associated with better functional capacity (improved by at least one NYHA class) [ 153 ], it was confirmed in a more recent study by Schoenenberger et al in which no change in walking time was observed in patients with improved left ventricular ejection fraction after thiamine supplementation period [ 165 ]. This raises questions about the real usefulness of thiamine supplementation in HF therapy, especially as other trials failed to demonstrate any benefit of vitamin B1 (dose ranging from 100 mg to 300 mg per day) although thiamine circulating level increased [ 15 , 166 , 167 , 168 ]. These studies not only failed to show a beneficial effect on cardiac function (FE) [ 15 , 167 ] but also failed to show an improvement in the quality of life of HF patients [ 15 , 166 , 167 , 168 ].…”
Section: B Vitamins In Heart Failurementioning
confidence: 99%
“…This raises questions about the real usefulness of thiamine supplementation in HF therapy, especially as other trials failed to demonstrate any benefit of vitamin B1 (dose ranging from 100 mg to 300 mg per day) although thiamine circulating level increased [ 15 , 166 , 167 , 168 ]. These studies not only failed to show a beneficial effect on cardiac function (FE) [ 15 , 167 ] but also failed to show an improvement in the quality of life of HF patients [ 15 , 166 , 167 , 168 ]. So far, the evaluation of thiamine supplementation as a new tool in HF therapeutics has shown mixed results and conclusions from the aforementioned studies are not clear because of the small sample size, short duration of follow-up, lack of any dietary assessment of thiamine intake, as well as the lack of precisely defined inclusion criteria.…”
Section: B Vitamins In Heart Failurementioning
confidence: 99%